2014
DOI: 10.1007/978-3-642-45195-9_13
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene for the Prevention and Treatment of Prostate Disease

Abstract: Benign prostatic hyperplasia (BPH) and prostate cancer are common diseases of the prostate gland. BPH is commonly treated by pharmaceutical products, which commonly improve symptoms but are often off-set by adverse events including erectile dysfunction, which affect quality of life. Similarly, a variety of treatment options exist for the treatment of prostate cancer. The applicability of these prostate cancer treatments is reliant on stage of disease. Whilst effectiveness of prostate cancer treatments may vary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The findings of the present work are important since it has been reported that only higher doses of maca or lycopene alone are required to induce significant inhibition on BPH (Gasco et al , ; Gonzales et al , ; Gonzales et al , ; Ilic, ). Since the effect of maca aqueous extract and benzyl glucosinolate have a similar effect on reducing PW, DHT, PAP levels, and serum testosterone/estradiol ratio, and according to data from the HPLC study, the content of benzyl glucosinolate in maca aqueous extract is 1.44 mg/kg the same fed to benzyl glucosinolate group, it is possible that benzyl glucosinolate is the active principle of maca aqueous extract on prostate hyperplasia.…”
Section: Resultsmentioning
confidence: 54%
“…The findings of the present work are important since it has been reported that only higher doses of maca or lycopene alone are required to induce significant inhibition on BPH (Gasco et al , ; Gonzales et al , ; Gonzales et al , ; Ilic, ). Since the effect of maca aqueous extract and benzyl glucosinolate have a similar effect on reducing PW, DHT, PAP levels, and serum testosterone/estradiol ratio, and according to data from the HPLC study, the content of benzyl glucosinolate in maca aqueous extract is 1.44 mg/kg the same fed to benzyl glucosinolate group, it is possible that benzyl glucosinolate is the active principle of maca aqueous extract on prostate hyperplasia.…”
Section: Resultsmentioning
confidence: 54%
“… 4 Studies have shown a strong correlation between sexual dysfunction and the severity of LUTS. 5 Pharmacological treatments are available for management of symptoms but can be expensive and may be associated with adverse events 6 ; lifestyle modifications therefore become the primary treatment strategies for improvement of prostate health due to its noninvasive and modifiable properties. 7 …”
Section: Introductionmentioning
confidence: 99%
“…Lycopene promotes good health owing to its therapeutic, prophylactic, and nutraceutical functions. Increasing scientific evidence displays its implications in carcinogenic cell apoptosis and cell cycle arrest of diverse types of human cancers [ 5 , 6 , 7 , 8 ]. Lycopene is also recognized as a strong cancer chemo-preventive agent [ 9 , 10 ] and has been found to have cardio-protective, antioxidant, and anti-inflammatory effects [ 11 ].…”
Section: Introductionmentioning
confidence: 99%